The Strength of a Solution Seeking Approach Editorial - Astrid Gynnild (Grounded Theory Review: An International Journal)
Why do PhD candidates choose grounded theory as their methodological approach? Many novice grounded theorists obviously grapple with this question while working on their dissertations. The Grounded Theory Review constantly receives papers from novice GT researchers that discuss and share experiences when following the tenets of the methodology.